Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007575
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for nausea and vomiting in early pregnancy

Abstract: Background Nausea, retching and vomiting are very commonly experienced by women in early pregnancy. There are considerable physical and psychological effects on women who experience these symptoms. This is an update of a review of interventions for nausea and vomiting in early pregnancy previously published in 2003. Objectives To assess the effectiveness and safety of all interventions for nausea, vomiting and retching in early pregnancy, up to 20 weeks' gestation. Search methods We searched the Cochrane Pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 47 publications
1
110
0
4
Order By: Relevance
“…Although women with HG have increased rates of low birth weight (LBW) babies, small for gestational age babies, preterm birth, and poor 5-min Apgar scores ( 31 ), outcomes are generally favorable ( 32,33 ). Management of HG is supportive, however, given the risk for electrolyte abnormalities and dehydration, hospitalization is not infrequent ( 34,35 ).…”
Section: First Trimestermentioning
confidence: 99%
See 1 more Smart Citation
“…Although women with HG have increased rates of low birth weight (LBW) babies, small for gestational age babies, preterm birth, and poor 5-min Apgar scores ( 31 ), outcomes are generally favorable ( 32,33 ). Management of HG is supportive, however, given the risk for electrolyte abnormalities and dehydration, hospitalization is not infrequent ( 34,35 ).…”
Section: First Trimestermentioning
confidence: 99%
“…Pregnant women with suspected portal hypertension should undergo screening with upper endoscopy for esophageal varices in the second trimester (strong recommendation, low level of evidence). 35. Pregnant women who are found to have large esophageal varices should be treated with beta-blockers and/or band ligation (conditional recommendation, very low level of evidence).…”
Section: Hepatitis C (Hcv)mentioning
confidence: 99%
“…Two Cochrane reviews were published recently. 62,63 Matthews et al 62 included only RCTs focusing on nausea and vomiting and excluded trials involving hyperemesis gravidarum; the review by Boelig et al 63 only included RCTs of hyperemesis gravidarum. Neither review categorized therapies depending on symptom severity.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Flavonoids, tannins and sesquiterpenes (-bisabolol and farnesene) (Minaiyan et al 2010;Aboul et al 2012;Afifi & Kasabri 2014); coumarins, phenolic compounds, polyacetylenes, flavones, flavonols and flavonones Aboul et al 2012); Essential oil (monoterpenes), triterpenes and fatty acids (Capuzzo et al 2014). Chamomile is used as anti-nausea and antiemtic in early pregnancy (Bishop et al 2011;Matthews et al 2014) or throughout pregnancy (Broussard et al 2010;Holst et al 2011). A higher incidence of threatening miscarriages and preterm labors was observed among regular pregnant users of chamomile (Cuzzolin et al 2010).…”
Section: Herbal Remedies With Female Antifertility and Abortificiant mentioning
confidence: 99%
“…It used to treat dysmenorrhea and delayed menses (Flores & Quinlan 2014). Clinical studies showed that Matricaria aurea (Chamomile) is used for nausea and vomiting intervention in early pregnancy (Bishop et al 2011;Matthews et al 2014) or throughout pregnancy (Broussard et al 2010;Holst et al 2011). A higher incidence of threatening miscarriages and preterm labors was observed among regular pregnant users of chamomile (Cuzzolin et al 2010).…”
Section: Herbal Remedies Of Fertility Pregnancy-related Issues and mentioning
confidence: 99%